Common Size Method For Measuring Financial Performance At PT. ABCD - Bramastyo Kusumo; Ali Muhdor (International Journal of Economics and Management Sciences, 2024)
This study's objective is to evaluate PT. ABSD financial results. The method used in this study is descriptive qualitative. The study's findings indicate that the company's financial performance as seen in the balance sheet statement is deemed unhealthy due to the lower liquidity value in terms of balance sheet assets. However, because businesses can raise cash and lower financial risk, income statements are seen negatively. In summary, despite the fact that the gross profit margin is declining annually, the income statement's financial performance is deemed unhealthy.